2015
DOI: 10.1128/jcm.00670-15
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis of Urinary Tract Infection and Underdiagnosis of Sexually Transmitted Infection in Adult Women Presenting to an Emergency Department

Abstract: dUrinary tract infections (UTIs) and sexually transmitted infections (STIs) are commonly diagnosed in emergency departments (EDs). Distinguishing between these syndromes can be challenging because of overlapping symptomatology and because both are associated with abnormalities on urinalysis (UA). We conducted a 2-month observational cohort study to determine the accuracy of clinical diagnoses of UTI and STI in adult women presenting with genitourinary (GU) symptoms or diagnosed with GU infections at an urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 25 publications
1
74
1
Order By: Relevance
“…As known, the chlamydia and mollicutes have a stimulating action on the lymphocytic reactions stipulating the progressive fibrinosis development. In contrary, the classical microbe agents, e.g., gonococci, trichomonads and other bacteria, stimulate the development of the coarse pyogenic processes [9,37,38]. In case of infecting by the mycoplasma, ureaplasma and/or gardnerella, the infection inflammatory process could proceed at a certain agent concentration and disorders in the microorganism immune protection only.…”
Section: Favorable Factors For Exacerbation Of Genital and Urinary Inmentioning
confidence: 99%
“…As known, the chlamydia and mollicutes have a stimulating action on the lymphocytic reactions stipulating the progressive fibrinosis development. In contrary, the classical microbe agents, e.g., gonococci, trichomonads and other bacteria, stimulate the development of the coarse pyogenic processes [9,37,38]. In case of infecting by the mycoplasma, ureaplasma and/or gardnerella, the infection inflammatory process could proceed at a certain agent concentration and disorders in the microorganism immune protection only.…”
Section: Favorable Factors For Exacerbation Of Genital and Urinary Inmentioning
confidence: 99%
“…One recent study examined the frequency of overdiagnosis of UTI and missed diagnostic opportunities for STIs with similar symptomatology, including gonorrhea, chlamydia, and trichomoniasis, in women presenting to the emergency department. The authors found that <50% of women who received a clinical diagnosis of UTI had a positive urine culture, whereas 37% of women with an STI were not diagnosed or treated (22).…”
Section: Emerging Uropathogensmentioning
confidence: 99%
“…Overdiagnosis has been described in relation to an increasing number of conditions outwith cancer screening (Harris, ; Martin, Boucher, Wright, & Saini, ; Tomas, Getman, Donskey, & Hecker, ; Wiener, Schwartz, & Woloshin, ; Yudkin & Montori, ). Of the six recognised drivers, four are relevant to cancer in primary care: expanded disease definitions; health system incentives favouring more tests and treatments; technological changes detecting ever smaller “abnormalities”; and cultural beliefs that more is better (a faith in early detection unmodified by its risks) (Moynihan, Doust, & Henry, ).…”
Section: Does Overdiagnosis Occur Outside Of Screening?mentioning
confidence: 99%
“…Overdiagnosis has been described in relation to an increasing number of conditions outwith cancer screening (Harris, 2015;Martin, Boucher, Wright, & Saini, 2014;Tomas, Getman, Donskey, & Hecker, 2015;Wiener, Schwartz, & Woloshin, 2013;Yudkin & Montori, 2014).…”
Section: Does Overdiagnosis Occur Outside Of Screening?mentioning
confidence: 99%